Fournier's gangrene": an uncommon differential diagnosis and complication of "Bartholin abscess - Seyedeh Houra Mousavi Vahed; Malihe Afiat; Mansoure Mottaghi; Seyed Mostafa Pashang; Atefe Alamatian (Mashhad University of Medical Sciences, 2017)
Introduction: Necrotizing Fasciitis is one type of necrotizing soft tissue infections involving fascia and overlying subcutaneous fat, it has fast development and results in fulminant tissue destruction, toxicity, sepsis and high mortality. "Fournier's gangrene" is another name for "Necrotizing fasciitis of perineum". Signs and symptoms are seveer pain, swelling, erythema and induration of major labia that spreads rapidly to the anterior abdominal wall and gluteal region. Clinical manifestations of early stage of "Fournier's gangrene" are similar to "Bartholine abscess". Since Bartholin abscess is common and "Fournier's gangrene" is rare, gynecologist, usually does not consider this diagnosis. Case presentation: A 52 year - old woman with fever and pain, erythema and swelling of valva was admitted to the hospital. Initially, her diagnosis was bartholine abscess and drainage and marsupialization was done to her. Since fever continued, pain and mal- odor discharge didn't improve, erythema and swelling progressed to mons of pubis and RLQ[S1] , thus with diagnosis of Fournier's gangrene, she underwent surgical exploration and debridement together with broad spectrum antibiotic therapy; she discharged two weeks later with good condition and no fever. Conclusion: Since early stages of "fournier's gangrene" can be mistaken with "Batholine abscess", gynecologist should consider fournier's gangrene in women with underlying medical conditions such as diabetes and immunodeficiency with urogenital infection."Fourneir's gangrene" is a surgical emergency, therefore early diagnosis and treatment can prevent morbidity and mortality.